If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 6 = 8 + 5p Reorder the terms: 6 + 6p = 8 + 5p Solving 6 + 6p = 8 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 6 + 6p + -5p = 8 + 5p + -5p Combine like terms: 6p + -5p = 1p 6 + 1p = 8 + 5p + -5p Combine like terms: 5p + -5p = 0 6 + 1p = 8 + 0 6 + 1p = 8 Add '-6' to each side of the equation. 6 + -6 + 1p = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 1p = 8 + -6 1p = 8 + -6 Combine like terms: 8 + -6 = 2 1p = 2 Divide each side by '1'. p = 2 Simplifying p = 2
| 2x+1=-1+6x+10 | | 91-73=27y-36y | | 4(3x+2)=0 | | 8m=0 | | 12-4x=24 | | (5n-1)(7n-10)=0 | | -18=9x | | 1780=.04x | | 6w+3w^2=144 | | 520=200x | | 13n-25+4=176 | | 13-25+4=176 | | x^2=-x | | .07x(18-x)=9 | | .07x(18-x)= | | 8x^2-16=0 | | 2u^2-12u+41=2(u-7) | | 9x-10=6x+29 | | 18-x+36=47 | | 112=-16t^2+96t+112 | | 2(x-3)=9-3x | | 5+9= | | 3x^2+2x-144=0 | | x^4+4x^3-5x^2-16x+4=0 | | 2(-4y^2)= | | 38(12-4.5x)=12(4x-10)+28.5 | | 16m-9n+2m+11n= | | x(5x+19)=4 | | 4(d+5.2)=10d-6.2 | | 7x+6y=-2 | | 0=16t^2+3 | | k^2+9k+8=0 |